Effect of Omega-3 on HLA-DR Expression by Conjunctival Cells and Tear Cytokine Concentrations in the Dry Eye Assessment and Management Study. Issue 9 (30th September 2022) - Roy, Neeta S.; Yu, Yinxi; Ying, Gui-Shuang; Maguire, Maureen G.; Asbell, Penny A.; ,
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To determine effect of omega-3 supplementation on conjunctival cell HLA-DR expression and tear concentrations of interleukin (IL)-1β, IL-6, IL-8, IL-10, IL-17A, interferon-γ, and tumor necrosis factor-α in dry eye disease patients in the Dry Eye Assessment and Management study. Methods: Patients were randomized to receive a daily dose of eicosapentaenoic and docosahexaenoic acids (ω3) or refined olive oil (placebo) for 12 months. At baseline, 6 and 12 months, HLA-DR expression in conjunctival total, epithelial, and white blood cells and cytokine concentration in tears were determined. Differences in change from baseline between treatment groups were assessed using generalized estimating equations (HLA-DR) or Wilcoxon rank–sum test (cytokines). Results: No differences were observed in HLA-DR expression in total, epithelial, or white blood cells between ω3 and placebo groups at 6 months (n=435) or 12 months (n=436). The median concentration percent change differed between ω3 and placebo groups at 6 months for IL-6 (−36.6 vs. 24.5%, P =0.02, n=75) and for IL-8 (3.7% vs. 72.6%, P =0.02, n=68); at 12 months, they did not differ ( P ≥0.18). No other differences between the treatment groups were detected. Conclusions: ω3 supplementation did not consistently affect ocular inflammatory status as measured by the frequency of HLA-DR expressing conjunctival cells or tear cytokines.